In vitro selective inhibition of human UDP-glucuronosyltransferase (UGT) 1A4 by finasteride, and prediction of in vivo drug–drug interactions. Issue 2 (22nd January 2015) - Lee, Seung Jun; Park, Jung Bae; Kim, Doyun; Bae, Soo Hyeon; Chin, Young-Won; Oh, Euichaul; Bae, Soo Kyung
Highlights: To our knowledge, inhibition of hepatic UGT isozymes by finasteride has not been explored. Of the seven hepatic UGTs, finasteride potently and selectively inhibited UGT1A4. Finasteride did not inhibit hepatic UGT1A1, 1A3, 1A6, 1A9, 2B7, and 2B15 activities. However, the C max of finasteride in patients is much lower than K i of finasteride for UGT1A4. Finasteride is unlikely to cause clinically significant drug–drug interactions via UGTs inhibition. Abstract: In the present study, we evaluated the inhibitory potentials of finasteride for the major human hepatic UDP-glucuronosyltransferases (UGTs) (UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A9, UGT2B7, and UGT2B15) in vitro using LC–MS/MS by specific marker reactions in human liver microsomes (except for UGT2B15) or recombinant supersomes (UGT2B15). Of the seven tested UGTs, finasteride potently, selectively, and competitively inhibited UGT1A4-mediated trifluoperazine- N -glucuronidation in human liver microsomes with an IC50 value of 11.5 ± 1.78 μM and K i value of 6.03 ± 0.291 μM. This inhibitory potency was similar to that of hecogenin, a well-known inhibitor of UGT1A4. However, finasteride did not seem to inhibit any of the other six UGTs: UGT1A1, UGT1A3, UGT1A6, UGT1A9, UGT2B7, or UGT2B15. Similarly, finasteride markedly inhibited UGT1A4 activity in recombinant human UGT1A4 supersomes, with a K i value of 6.05 ± 0.410 μM. In addition, finasteride strongly inhibited UGT1A4-catalyzed imipramine -N -β-d -glucuronidation. However, on the basis of an in vitro–in vivo extrapolation, our data strongly suggested that finasteride is unlikely to cause clinically significant drug–drug interactions mediated via inhibition of the hepatic UGT enzymes involved in drug metabolism in vivo .